1978
DOI: 10.1002/chin.197805090
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ION EXCHANGER‐CATALYZED ADDITION OF ALKENES TO ALCOHOLS

Abstract: Die durch Ionex katalysierte Addition von Isobutylen an Methanol oder Ethanol wird im Labormaßstab vor allem im Hinblick auf Reaktionsbedingungen, Seitenreaktionen und Katalysatoreigenschaften untersucht, Wird die Reaktion im Autoklaven durchgeführt, so sinkt der Isobutylen‐ Oligomeren‐Anteil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The reaction of MTBE synthesis has been considered suitable for our purposes because it is a reversible and fairly exothermic reaction (A7f°(298 K) = -15.63 kcal• mol"1). The MTBE is obtained from the reaction of addition of methanol to isobutene catalyzed by sulfonic ion-exchange resins with high selectivity, in both the liquid and vapor phases (Ancillotti et al, 1978;Setinek et al, 1977;Heck et al, 1981). In addition there is currently great interest in MTBE because of its remarkable antiknock properties (Reynolds et al, 1975;Garibaldi et al, 1977; Taniguchi and Johnson, 1979; Talbot, 1979;Harrington et al, 1979;Csikos et al, 1980;Farhat and Mazhar, 1984…”
Section: General Researchmentioning
confidence: 99%
“…The reaction of MTBE synthesis has been considered suitable for our purposes because it is a reversible and fairly exothermic reaction (A7f°(298 K) = -15.63 kcal• mol"1). The MTBE is obtained from the reaction of addition of methanol to isobutene catalyzed by sulfonic ion-exchange resins with high selectivity, in both the liquid and vapor phases (Ancillotti et al, 1978;Setinek et al, 1977;Heck et al, 1981). In addition there is currently great interest in MTBE because of its remarkable antiknock properties (Reynolds et al, 1975;Garibaldi et al, 1977; Taniguchi and Johnson, 1979; Talbot, 1979;Harrington et al, 1979;Csikos et al, 1980;Farhat and Mazhar, 1984…”
Section: General Researchmentioning
confidence: 99%
“…In vapor phase the chemical equilibrium is not favorable at temperatures higher than 100 °C (Iborra et al, 1989), but selectivity and yield in ether are rather good on sulfonated resins at 85-100 °C and atmospheric pressure (Setinek et al, 1977). In spite of that no kinetic study has been found in open literature.…”
Section: Introductionmentioning
confidence: 98%